Knowledge and systems sciences : 17th International Symposium, KSS 2016, Kobe, Japan, November 4-6, 2016, Proceedings /: 17th International Symposium, KSS 2016, Kobe, Japan, November 4-6, 2016, Proceedings. (2016) - Unknown
No abstract available